Inhibition of insulin/IGF‐1 receptor signaling protects from mitochondria‐mediated kidney failure. Issue 3 (2nd February 2015) - Ising, Christina; Koehler, Sybille; Brähler, Sebastian; Merkwirth, Carsten; Höhne, Martin; Baris, Olivier R; Hagmann, Henning; Kann, Martin; Fabretti, Francesca; Dafinger, Claudia; Bloch, Wilhelm; Schermer, Bernhard; et al.
<x xml:space="preserve">Abstract</x> Podocyte‐specific PHB2 loss results in severe kidney disease that is alleviated by insulin and IGF‐1 receptors deletion or rapamycin treatment, demonstrating not only a causal link between mitochondrial dysfunction and kidney disease but also putative therapeutic avenues. <boxed-text content-type="graphic" id="emmm201404916-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>